The Diagnostic Yield of Cone-Beam Computed Tomography for Degenerative Changes of the Temporomandibular Joint in Dogs - McKay, Rachel Marie; Vapniarsky, Natalia; Hatcher, David; Carr, Nicole; Chen, Shuai; Verstraete, Frank J. M.; Cissell, Derek D.; Arzi, Boaz (Frontiers in Veterinary Science, 2021)
Degenerative changes of the temporomandibular joint (DTMJ) may be diagnosed via cone - beam computed tomography (CBCT). However, despite advancement in CBCT imaging, correlation of DTMJ features identified on CBCT with gross and histological findings is currently limited. This study aimed to correlate CBCT findings of DTMJ of dogs with gross and histopathologic changes. Temporomandibular joints (TMJ) (n = 38) from fresh cadaver heads of asymptomatic dogs (n = 19) were examined radiologically, macroscopically, and microscopically. Association of CBCT - detected DTMJ changes with gross and histological findings were statistically evaluated via kappa statistics and ordinal logistic mixed-effects models. The radiological changes observed on CBCT included joint space narrowing, subchondral/cortical bone changes (i.e., erosions or lysis), osteophytes, and subchondral bone sclerosis. Upon macroscopic evaluation, the majority of examined specimens had mild changes with cartilage defects and osteophytes affecting <10% of the total articular surface area. Histopathologic changes comprised splitting and degeneration of the fibrous cartilage layers, subchondral bone exposure, subchondral bone sclerosis, focal subchondral bone lysis, and occasional cell death. Subchondral sclerosis was the most prevalent finding radiologically and histologically with a fair to excellent agreement. Importantly, the more severe the TMJ degenerative changes, the higher the agreement between CBCT and histology. Based on the correlative results of statistical analysis, CBCT was found to be a suitable modality to evaluate DTMJ.